2016
DOI: 10.1007/s00339-016-9829-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of boron-doped nanocrystalline diamond-coated MEMS probes

Abstract: Fabrication processes of thin boron-doped nanocrystalline diamond (B-NCD) films on silicon-based micro-and nano-electromechanical structures have been investigated. B-NCD films were deposited using microwave plasma assisted chemical vapour deposition method. The variation in B-NCD morphology, structure and optical parameters was particularly investigated. The use of truncated cone-shaped substrate holder enabled to grow thin fully encapsulated nanocrystalline diamond film with a thickness of approx. 60 nm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Accordingly, V D ranges from – 0.4 to 1 eV for the Co tip which agrees, for example, to the shift of surface potential observed for adsorbed hydrogen on Co films (Duś & Lisowski, 1976); and (iii) in literature, the work function of conductive diamond films used for AFM probe coatings, i.e. Φ cd,bulk , varies from 3.5 to 5.5 eV depending on the doping level and surface treatments (Maier et al ., 2001; Bogdanowicz et al ., 2016) and, in accordance, the potential drop V D for the cd tip ranges from – 0.39 to 1.61 eV that is in agreement to previous studies (Volodin et al ., 2007).…”
Section: Efm‐phase Measurementssupporting
confidence: 93%
“…Accordingly, V D ranges from – 0.4 to 1 eV for the Co tip which agrees, for example, to the shift of surface potential observed for adsorbed hydrogen on Co films (Duś & Lisowski, 1976); and (iii) in literature, the work function of conductive diamond films used for AFM probe coatings, i.e. Φ cd,bulk , varies from 3.5 to 5.5 eV depending on the doping level and surface treatments (Maier et al ., 2001; Bogdanowicz et al ., 2016) and, in accordance, the potential drop V D for the cd tip ranges from – 0.39 to 1.61 eV that is in agreement to previous studies (Volodin et al ., 2007).…”
Section: Efm‐phase Measurementssupporting
confidence: 93%
“…42,43 From the linear relation, the PZCs of graphite (work function: 4.6−4.7 eV) 44,45 and graphene (work function: 4.6 eV) 45−47 were, respectively, calculated to be −0.1 to 0.0 V and −0.1 V, which are fairly consistent with the experiments. Because the work function of the sp 3 diamond structure of BDD was reported to be 4.650 to 5.165 eV, 48,49 it is reasonable that the PZC of BDD would be more positive than that of graphite or graphene. Therefore, we concluded that the PZC of BDD in the range of 0.0−0.2 V from our experiment is reliable to verify this unique experimental setup.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The substrates were seeded with mono‐dispersed nanodiamond suspension in ultrasonic bath for 30 min . A special truncated cone‐shaped shim was used during the growth of diamond films . In this study, the molar ratio of CH 4 H 2 mixture was kept at 1% of gas volume at 300 sccm of the total flow rate.…”
Section: Methodsmentioning
confidence: 99%